Applying science to pressing conservation needs for penguins. Issue 1 (13th August 2019) - Boersma, P.D.; Borboroglu, P. García; Gownaris, N.J.; Bost, C.A.; Chiaradia, A.; Ellis, S.; Schneider, T.; Seddon, P.J.; Simeone, A.; Trathan, P.N.; Waller, L.J.; Wienecke, B.
Abstract: More than half of the world's 18 penguin species are declining. We, the Steering Committee of the International Union for Conservation of Nature Species Survival Commission Penguin Specialist Group, determined that the penguin species in most critical need of conservation action are African penguin (Spheniscus demersus), Galápagos penguin (Spheniscus mendiculus), and Yellow‐eyed penguin (Megadyptes antipodes) . Due to small or rapidly declining populations, these species require immediate scientific collaboration and policy intervention. We also used a pairwise‐ranking approach to prioritize research and conservation needs for all penguins. Among the 12 cross‐taxa research areas we identified, we ranked quantifying population trends, estimating demographic rates, forecasting environmental patterns of change, and improving the knowledge of fisheries interactions as the highest priorities. The highest ranked conservation needs were to enhance marine spatial planning, improve stakeholder engagement, and develop disaster‐management and species‐specific action plans. We concurred that, to improve the translation of science into effective conservation for penguins, the scientific community and funding bodies must recognize the importance of and support long‐term research; research on and conservation of penguins must expand its focus to include the nonbreeding season and juvenile stage; marine reserves must be designed at ecologically appropriate spatial and temporal scales; and communication between scientists and decision makers must be improved with the help of individual scientists and interdisciplinary working groups. Abstract : Article impact statement : Safeguarding the future of penguins requires collaboration among scientists and policymakers and immediate, informed conservation action. Abstract : Aplicación de Ciencia en las Necesidades de Conservación Urgentes para los Pingüinos. Resumen: Más de la mitad de las 18 especies de pingüinos del mundo están disminuyendo. Nosotros, el Comité Directivo de la Unión Internacional para la Conservación de la Naturaleza, Grupo de Especialistas en Pingüinos, determinamos que las especies de pingüinos con necesidades críticas de conservación son el pingüino africano ( Spheniscus demersus ), el pingüino de las Galápagos ( Spheniscus mendiculus ) y el pingüino de ojos amarillos ( Megadyptes antipodes ). Debido a que sus poblaciones son pequeñas o están declinando rápidamente, estos pingüinos requieren colaboración científica e intervención política inmediatas. También utilizamos un método de clasificación por pares para priorizar las necesidades de investigación y conservación para todas las especies de pingüinos. Entre las 12 áreas de investigación que identificamos, las más prioritarias fueron: cuantificación de las tendencias poblacionales, estimación de las tasas demográficas, predicción de las patrones de cambio ambiental y mejora del conocimiento de las interacciones con pesquerías. Las mayores necesidades de conservación fueron: optimizar la planificación marina espacial, mejorar la colaboración de las partes interesadas y desarrollar planes de manejo de desastres y de acción para cada especie. Coincidimos en que, para mejorar la traducción de la ciencia en la conservación efectiva de los pingüinos, la comunidad científica y los organismos financiadores deben reconocer la importancia de la investigación a largo plazo y apoyarla; la investigación sobre pingüinos y su conservación debe expandir su enfoque para incluir la época no reproductiva y la etapa juvenil; las reservas marinas deben ser diseñadas a escalas espaciotemporales ecológicamente apropiadas; y la comunicación entre científicos y tomadores de decisiones debe mejorar con la ayuda de científicos individuales y grupos de trabajo interdisciplinario.